Forensic Archaeology Multidisciplinary Perspectives - Moran, Kimberlee Sue.; Gold, Claire L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the multidisciplinary field of forensic archaeology as complementary but distinct from forensic anthropology. By looking beyond basic excavation methods and skeletal analyses, this book presents the theoretical foundations of forensic archaeology, novel contexts and applications, and demonstrative case studies from practitioners active in the field. Many of the chapters present new approaches and methods not previously covered in other forensic archaeology books, some of which may be of direct use to those conducting criminal investigations. .
Part 1 - Theoretical Frameworks -- Different but equal: the philosophical foundations of forensic archaeology -- Four-Field Forensic Archaeology -- Professionalism in Forensic Archaeology: Transitioning from 'Cowboy of science' to 'officer of the court' -- Forensic Archaeologist or Crime Scene Investigator? -- The Human Side of Forensic Archaeology -- Part 2 - Forensic Archaeological Contexts -- The Language of Forensic Archaeology: Discourses in Field and in Court -- Convincing LEO: Successful interaction between the archaeologist and law enforcement officials in crime scene investigations -- The Use of Forensic Archaeology in Missing Person Cases -- Landfill Searches for Human Remains -- The Application of archaeological techniques to forensic fire scenes -- An Evolving Problem for Forensic Archaeology: The Involvement of Armed Users of Controlled Substances in Archaeological Crime -- Part 3 - Multi-disciplinary Techniques & Methods -- The Role of Palynology in Forensic Archaeology -- Chemistry & Forensic Archaeology - A Marriage Made in Heaven -- The Use of 3D Laser Scanning in Forensic Archaeology to Document Unauthorized Archaeological Damage -- Forensic Archaeology and the Question of Using Geographic Profiling Methods such as "Winthropping" -- Part 4 - Case Studies -- The Benefits of a Cooperative Approach: Case Studies from Lancaster County, Nebraska -- Digging, Defacement, Damage, and Dealing: Case Studies of the Role of Forensic Archaeology in Archaeology -- Looking Back: 10 Years after "The Station" Nightclub Fire, West Warwick, Rhode Island -- Acquisition and Disposition Problems and Experiences Policing the Online Marketplace for Human Remains -- Take Them to the Woods: Melding Forensic Education with Real Case Experience.
Keywords: Archaeology; Anthropology; Forensic sciences; Archaeology; Anthropology; Forensic Science